Raman spectroscopy and correlative‐Raman technology excel as an optimal stage for carbon‐based electrode materials in electrochemical energy storage. (15th June 2021) - Zheng, Ying; Deng, Ting; Yue, Nailin; Zhang, Wei; Zhu, Xuanbo; Yang, He; Chu, Xianyu; Zheng, Weitao
Abstract: The structural details of carbon materials directly affect their properties as an electrode material, such as specific capacitance and coulomb efficiency. Therefore, the structural analysis of carbon materials has always been an important step in the mechanistic insight into their roles in electrochemical energy storage. Raman spectroscopy, as molecular spectroscopy technique, has been widely used in understanding the lattice vibration mechanics of carbon materials and providing information on the chemical structure at molecular level, as well as microstructure analysis of carbon materials. In addition, the development of correlative‐Raman technology enables clarifying more comprehensive and accurate structural information for carbon‐based materials. With this information, it is of great significance to guide the construction of advanced carbon‐based electrode materials for energy storage. Abstract : In this review, the application and potential of Raman spectroscopy in the research of carbon‐based energy storage electrode materials are reviewed. Our paper briefly reviewed the principle of Raman's research on carbon materials and summarized the application of Raman spectroscopy in carbon materials with different energy storage mechanisms.